PENGARUH PIJAT BAYI TERHADAP KUANTITAS TIDUR BAYI DI DESA BEDADUNG KECAMATAN SUMBERSARI KABUPATEN JEMBER - Harianah Akib; Nuning Dwi Merina (Lembaga Penelitian dan Pengabdian Masyarakat Universitas dr. Soebandi, 2018)
Sleep for babies is a top priority, because when sleeping in infants growth and development of the baby is optimal. 80% of infants find it difficult to sleep at night, often wake up more than 1 hour at night, sleep at night less than 9 hours, total sleep less than 13 hours / day, and only 20% have normal hours of sleep with an average of 14 hours / day. Considering the importance of sleep time for babies, sleep needs must be met, one of the methods used is by infant massage. This research was conducted to determine the effect of infant massage on the quantity of infant sleep. The research method uses pre-experimental design with one group pretest posttest design. The population in this study were infants aged 3-6 months in the Village of Bedadung, Sumbersari District, Jember Regency with a total of 25 infants. The sample in this study were 23 infants, with the sampling technique used was simple random sampling. Data analysis used paired sample t-test, with a confidence level of 95% (α <0.05). The results showed that babies who were massaged 3 times / week in 1 week, the average quantity of sleep babies before doing baby massage was 12.52 hours / day, the average quantity of baby sleep after baby massage was 14.43 hours / day, with a p value of 0,000 <(α = 0.05) then Ha is accepted, there is the effect of infant massage on the quantity of sleep of infants aged 3-6 months in Bedadung Village, Sumbersari District, Jember Regency. It is recommended for mothers to still apply baby massage in accordance with the techniques that have been taught and to continue to do baby massage independently to meet their baby's sleep needs